Cybersecurity : a practical engineering approach - Santos, Henrique (Boca Raton CRC Press, 2022)
"Cybersecurity: A Practical Engineering Approach introduces the implementation of a secure cyber architecture, beginning with the identification of security risks. It then builds solutions to mitigate risks by considering the technological justification of the solutions as well as their efficiency. The process follows an engineering process model. Each module builds on a subset of the risks, discussing the knowledge necessary to approach a solution, followed by the security control architecture design and the implementation. The modular approach allows students to focus on more manageable problems, making the learning process simpler and more attractive"--
Includes bibliographical references and index.
Keywords: Computer networks; Computer security